Fe3O4@PEG-SO3H rod-like morphology along with the spherical nanoparticles: novel green nanocomposite design, preparation, characterization and catalytic application. Issue 112 (22nd November 2016) - Maleki, Ali; Zand, Pedram; Mohseni, Zahra
Abstract : A new heterogeneous nanocatalyst was successfully synthesized, completely characterized and efficiently applied in the synthesis of dihydropyrimidines. Abstract : The design and preparation of polyethylene glycol sulfonic acid surface coated magnetic nanoparticles (Fe3 O4 @PEG-SO3 H) is described. The morphology of the prepared nanocomposite was rod-like along with spherical nanoparticles. It was characterized by Fourier transform infrared (FT-IR) spectroscopy, field-emission scanning electron microscopy (FE-SEM), X-ray diffraction (XRD), energy-dispersive X-ray (EDX), vibrating sample magnetometry (VSM), N2 adsorption–desorption by Brunauer–Emmett–Teller (BET) and inductively coupled plasma (ICP) analysis. Furthermore, this novel heterogeneous catalyst was successfully used in a multicomponent one-pot reaction for the synthesis of dihydropyrimidine derivatives. This efficient protocol includes some other advantages such as using ethanol as a green solvent, no significant decrease in the activity of the nanocatalyst during the recovery process, relatively short reaction times and high-to-excellent yields of the products.